Portrayal of Women's Exploitation by Pakistani Female Writers: An Analysis of Selected Short Stories by Fahmida Riaz, Bina Shah, and Qaisra Shahraz: Kamla Bhasin's Understanding of Patriarchy - Mehak Dahiyo; Salma Naz (University of Chitral Journal of Linguistics and Literature, 2023)
This study is a feminist analysis of selected short stories such as Daughters of AAI by Fahmida Riaz, The Optimist by Bina Shah, The Elopement, The Discovery, and Perchanvah by Qaisra Shahraz in light of Bhasin's idea of Patriarchy. The study mainly focuses on the portrayal of women's exploitation presented by Pakistani female writers in their short stories through textual analysis with the help of close reading. It is found that women are exploited in many ways, as represented by writers in their short stories. The findings of this study include that social, economic, psychological, cultural, and physical exploitation of women is commonly practised in patriarchal institutions, and it has been realistically portrayed by Pakistani female writers to educate the readers. Based on this study, it is recommended that future researchers still have the space to work on these short stories with different frameworks to add something new to literary research.